PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) PADA MATERI ARITMATIKA SOSIAL - Duka, Aleksander; Arifendi, Rio Febrianto; Setiawan, Rudy; Irianti, Nathasa Pramudita (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2022)
Classroom Action Research (CAR) in two cycles aims to improve students' mathematics learning outcomes, especially social arithmetic, by using the Realistic Mathematics Education (RME) learning approach in class VIIC students of SMP Muhammadiyah. Student learning outcomes increase with an average value of 73.54 percent in the first cycle and 91.45 percent in the second cycle with a KKM value of 75, improving student learning outcomes by using the RME learning strategy in social arithmetic subjects. This shows that the RME strategy has been adequate and has succeeded in improving student learning outcomes, especially in mathematics. The findings of this study are expected to be useful in improving the quality of education with the RME approach in schools, especially mathematics.